2014
DOI: 10.1530/eje-13-0596
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose hydrocortisone replacement therapy is associated with improved bone remodelling balance in hypopituitary male patients

Abstract: Objective: Glucocorticoid (GC) therapy is associated with adverse effects on bone metabolism, yet the effects of different GC physiological replacement regimens in hypopituitarism are not well characterised. We aimed to assess the effect of three hydrocortisone (HC) replacement dose regimens on bone turnover. Study design: An open cross-over study randomising ten hypopituitary men with severe ACTH deficiency to three commonly used HC dose regimens: dose A (20 mg mane and 10 mg tarde), dose B (10 mg mane and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
(41 reference statements)
2
27
0
Order By: Relevance
“…Further, in the current study, BAP/urinary NTx ratio was significantly increased at 3 months and 3 years after TSS. Previous studies have reported that the ratio of procollagen type I N-propeptide (PINP) and C-terminal cross-linking telopeptide (CTX-I), other bone turnover markers, reflects the bone remodeling balance [8]. The increase of BAP/urinary NTx ratio after TSS in acromegalic patients suggests that bone formation is superior to bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in the current study, BAP/urinary NTx ratio was significantly increased at 3 months and 3 years after TSS. Previous studies have reported that the ratio of procollagen type I N-propeptide (PINP) and C-terminal cross-linking telopeptide (CTX-I), other bone turnover markers, reflects the bone remodeling balance [8]. The increase of BAP/urinary NTx ratio after TSS in acromegalic patients suggests that bone formation is superior to bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…During the admission, subjects took the predesignated HC dose at 0800, 1600 and 0800 h the following morning of the admission. All patients had a 24-h serum cortisol measurements on treatment as described previously (19,20). Ten healthy-matched controls underwent identical biochemical profiling to the patient group.…”
Section: Methodsmentioning
confidence: 99%
“…No patient had known diabetes mellitus (DM), two patients had controlled hypertension and were on stable doses of angiotensin-converting enzyme inhibitor medication that was not changed during the study. This patient population has been described in detail in prior publications from our group (19,20). Exclusion criteria were as described in previous publications (19,20), and with particular reference to this analysis, those with uncontrolled hypertension or a known diagnosis of DM were excluded.…”
Section: Patients and Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a recent German study on 57 patients showed a variation of 8-10 mg in the daily dose of hydrocortisone over 2 years had a significant impact on bone mineral density [19]. Behan et al showed, in an open crossover study looking at markers of bone turnover and three different doses of hydrocortisone (20-10/10-10/10-5 mg/day), that the weakest dose was associated with an increase in bone formation [20].…”
Section: Adult Patientsmentioning
confidence: 98%